Association of 2009 Pandemic Influenza A (H1N1) Infection and Increased Hospitalization With Parapneumonic Empyema in Children in Utah - Ampofo, Krow (2010)
BACKGROUND: During previous influenza pandemics, many deaths were associated with secondary bacterial infection. In April 2009, a previously unknown 2009 influenza A virus (2009 H1N1) emerged, causing a global influenza pandemic. We examined the relationship between circulating 2009 H1N1 and the occurrence of secondary bacterial parapneumonic empyema in children. METHODS: Children hospitalized with parapneumonic empyema from August 2004 to July 2009, including a period when the 2009 H1N1 circulated in Utah, were identified using International Classification of Diseases, Ninth Revision codes. We compared the average number of children diagnosed with influenza A and the number of admissions for empyema per month for the previous 4 seasons to rates of empyema during the 2009 H1N1 outbreak. We identified causative bacteria using culture and polymerase chain reaction (PCR). RESULTS: We observed an increase in hospitalization of children with pneumonia complicated by empyema during a severe outbreak of 2009 H1N1 during the spring and summer of 2009, compared with historical data for the previous 4 seasons. Streptococcus pneumoniae and Streptococcus pyogenes were the predominant bacteria identified. CONCLUSIONS: Similar to previous pandemics, secondary bacterial infection with S. pneumoniae and S. pyogenes were associated with the 2009 H1N1 outbreak. There is an urgent need to better understand bacterial complications of pandemic influenza. In the interim, influenza vaccines, antiviral agents, and pneumococcal vaccines should be used to prevent cases of secondary bacterial pneumonia whenever possible.